Assessing the risk of saltwater intrusion in coastal aquifers - Klassen, J.; Allen, D.M. (Journal of hydrology (Amsterdam), 2017)
•Mapping and validating the vulnerability of a coastal aquifer to saltwater intrusion.•Coastal hazards incorporate projected sea level rise and storm surge impact.•Risk is assessed based on cost to replace the water supply and economic loss in agricultural areas. In coastal regions, the quality of groundwater can be compromised due to saltwater intrusion (SWI) caused by natural (sea level rise (SLR) and storm surge) and anthropogenic (pumping) hazards. The goal of this research was to develop and test an approach for assessing the risk of SWI in coastal aquifers. The Gulf Islands in British Columbia (BC) was the case study area. The vulnerability of the bedrock aquifers to SWI was assessed spatially by mapping hazards in combination with the aquifer susceptibility. Climate change related hazards, including SLR and storm surge overwash, were integrated into floodplain maps for each island using projected SLR data for 2100 in combination with estimated storm surge levels based on data collected over a forty year period. When combined with maps showing the density of pumping wells, coastal zones that may be at higher risk of SWI were identified for this particular coastal area of BC. Hazards due to pumping have the greatest influence on the vulnerability. Risk was evaluated spatially using an economic valuation of loss – here replacement of a water supply. The combination of chemical indicators of SWI and risk assessment maps are potentially useful tools for identifying areas vulnerable to SWI, and these tools can be used to improve decision-making related to monitoring and community development for coastal areas, thereby increasing resilience.